THE IMPACT OF ROMANTIC LOVE MYTHS ON CYBER DATING VIOLENCE VICTIMIZATION AMONG EMERGING ADULTS IN RELATIONSHIPS - Yasnita, Chairunnisa; Rahayu Hardianti Utami (Causalita, 2024)
The development of social frameworks related to romantic love myths raises concerns about the acceptance of violence in relationships. This study aims to examine the influence of romantic love myths on cyber dating violence among early adults in relationships. A quantitative method was employed with a sample of 600 early adult participants, selected through purposive sampling based on the criteria of being 18–25 years old and having been or currently being in a relationship. The study used the Spearman’s rho rank test, which found that romantic love myths affect cyber dating violence in the control/monitoring dimension, with an R Square of 0.065 (6.5%) and a significance level of 0.000 (p < 0.05). These results quantitatively indicate that romantic love myths can increase cyber dating violence related to control/monitoring behaviors in early adults who are in relationships